Features of microelements accumulation in macroalgae of the coastal area of the Kuyalnyk Estuary and its tributaries (Northwestern Black Sea, Ukraine) - Shykhaleyeva, G.M.; Kiryushkina, H.M.; Gerasimyuk, V.P. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2025)
The article presents the concentrations of a number of trace elements (Al, Mn, Fe, Cu, Cd, Pb, Cr, Zn, V) in thalli of representatives Chlorophyta (genera Cladophora Kütz., Rhizoclonium Kütz., Ulotrhrix Kütz., Ulva L. emend. Thur.), Charophyta (genera Spirogyra L., Chara L.) and Xanthopyta (genus Vaucheria DC.) algae in different areas of the water area (at 14 stations) of the hyperhaline Kuyalnyk Estuary and its main tributaries (the Velikiy Kuyalnyk River, Peresypsky and Korsuntsivskyi ponds, streams on the right and left banks of the estuary) in the period of 2004–2017. Based on the results of synchronous studies of the content of metals in the thalli of macroalgae and their environment (water and bottom sediments), the accumulative ability of the studied macroalgae concerning the specified number of metals was revealed as well as statistically significant correlations between the concentrations of individual metals in the thalli of green algae, water, and bottom sediments. It has been shown that the accumulation of most trace elements by macroalgae thalli is influenced both by species specificity, the morphostructure of the thallus, and the concentration of trace elements in their growth environment, and probably the effect of their interaction, hydrochemical and hydrological conditions of the reservoir.